Theory of Interband Optical Absorption in Quantum Wells Based on Bulk Materials with Anisotropic Nonparabolic Bands - V.V.В Ivchenko; V.S.В Shcherbiuk (Журнал нано- та електронної фізики)
Theory of interband optical absorption in rectangular quantum well with infinite barriers based on materials with strong nonparabolicity and anisotropy of energy spectra is developed. The numerical calculations for three-dimensional Dirac cadmium arsenide are done. Special attention is paid to the investigation of the effects of energy gap oscillation and вЂњblue shift delayвЂќ in this material.